OpenFOAM Analysis on the Comparison of Safety Requirements Provided for Water-Air and LOX-He Storage Systems - Raj, Sarath; K.S., Bibin; K.E., Reby Roy (International Journal of Occupational Safety and Health, 2024)
Introduction: In storage vessels filled with cryogenic liquids thermal destratification can be effectively done by the continuous supply of bubble movements. Therefore, the pressure builds up subsequent blasting of such containers can be avoided and cryogenic storage vessels can be used safely. The Volume of Fluid (VOF) approach is utilized in the current computational analysis to examine the safety precautions, dynamics of bubble creation, and subsequent collapse of the free liquid surface in both vertically and horizontally aligned rectangular containers. Methods: In the present work, using the Volume of Fluid (VOF) method, numerically investigated the sloshing behavior within a rectangular container with a 15% free air space with double gas inlets. Results: The impact of inlet gas velocity on sloshing rate due to bubbling is investigated numerically. Also, comparative studies are carried out to investigate the variations of bubble diameter, detachment time, and bubble detachment frequencies considering water-air and LOX-He systems. The mixing behaviors in LOX due to helium bubble formation under different inlet gas velocities were also numerically investigated. The numerical results show that the average deformation index increased by 23.83% when the water-air system was replaced with the LOX-He system. Hence, it can be understood that for the storage vessels filled with cryogenic liquids more safety precautions have to be considered to avoid thermal stratification. The safety precautions include increasing the gas flow rate and including more number gas flow inlets. Conclusion: The present analysis concludes that under a given condition the free liquid surface deformation is more for the case where storage vessels filled with LOX-He. Hence, it can be understood that for the storage vessels filled with cryogenic liquids more safety precautions have to be considered to avoid thermal stratification. The safety precautions include increasing the gas flow rate and including more number gas flow inlets.